2010
DOI: 10.4269/ajtmh.2010.09-0125
|View full text |Cite
|
Sign up to set email alerts
|

Hospital-Based Surveillance for Japanese Encephalitis at Four Sites in Bangladesh, 2003–2005

Abstract: Abstract. We investigated the epidemiology and etiology of encephalitis at four tertiary hospitals in Bangladesh during [2003][2004][2005]. Patients who met a clinical case definition for acute encephalitis and had cerebrospinal fluid (CSF) pleocytosis were eligible for enrollment; a standardized sampling pattern was used to enroll eligible patients. Recent Japanese encephalitis virus (JEV) infection was defined by presence of IgM antibodies against JEV in CSF or serum. Twenty (4%) of 492 cases had laboratory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 20 publications
2
42
0
Order By: Relevance
“…The median age of patients is less than 10 years old among unvaccinated populations, with the majority of deaths occurring in this phase of childhood [83]. The duration of acute, nonlethal disease (DW = 0.616) is two to three weeks.…”
Section: Resultsmentioning
confidence: 99%
“…The median age of patients is less than 10 years old among unvaccinated populations, with the majority of deaths occurring in this phase of childhood [83]. The duration of acute, nonlethal disease (DW = 0.616) is two to three weeks.…”
Section: Resultsmentioning
confidence: 99%
“…[29][30][31] Identifying the highest JE incidence in the Rajshahi Medical College Hospital catchment area is consistent with the hospital-based JE study conducted in [2003][2004][2005], where over half of the cases (11 of 20) were identified from this hospital among four study hospitals. 9 A higher number of JE cases in Rajshahi may result from the local ecology. The mosquito vector of JE breeds prolifically in wet fields, especially in paddy fields.…”
Section: Discussionmentioning
confidence: 99%
“…8 A hospital-based study conducted from 2003 to 2005 to assess the etiologies of encephalitis at four hospitals in Bangladesh found that among 492 patients with clinical encephalitis, 20 (4%) cases had laboratory evidence of recent JEV infection. 9 The incidence of JE has been reduced dramatically in Japan, Korea, Taiwan, China, and Thailand since the introduction of a JE vaccine into the national immunization programs of these countries. [10][11][12][13][14] Widely used live attenuated SA 14-14-12 JE vaccine is inexpensive and with a single dose provides 80-96% protection.…”
Section: Introductionmentioning
confidence: 99%
“…The clinical case definition of acute encephalitis include new onset of fever (temparetureeˆ38 0 C) or history of fever during the present illness along with altered mental status (confusion, disorientation, coma) and/ or neurological deficit (focal or diffuse neurological dysfunction or new onset of seizure-either focal or generalized) 8 . Pyogenic meningitis was excluded by Cerebro-spinal fluid (CSF) study, culture, latex agglutination test and severe malarial cases were excluded by RDT (Rapid Diagnostic Test) for malaria positive or Blood slide examination (BSE) positive cases.…”
Section: Methodsmentioning
confidence: 99%
“…Two years hospital based surveillance in Bangladesh was found 4% JEV infection. 8 Encephalitis is a serious infection in children with usually no specific treatment and the mortality rate is also high. 9 It is endemic throughout the year with occasional epidemics in various localities in our country.…”
mentioning
confidence: 99%